Sharpshooters, Leafhoppers, Cicadellidae (Insecta: Hemiptera: Auchenorrhyncha: Cicadellidae) - Chris Tipping; Russell F. Mizell, III (EDIS)
Sharpshooter is a term commonly used to describe a group of leafhoppers in the family Cicadellidae. There have been several explanations for the use of this term. Riley and Howard (1893) first used 'sharpshooter' to describe the feeding damage of the glassy-winged sharpshooter, Homalodisca coagulata (Say), on cotton. This damage was caused by the piercing-sucking mouthparts of H. coagulata that appeared to be caused by a 'minute bullet.' They also reported 'rapid and forcible ejection of minute drops of fluid' as another explanation for the use of this term. The term sharpshooter is also attributed to the hiding behavior of these insects when alarmed. Disturbed sharpshooters will slip quickly behind branches and stems to avoid predators, an action not unlike the behavior of army sharpshooter riflemen who would hide behind the trunks of trees to avoid detection by the opposition as they passed by their position. This document is EENY-334 , one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2004.